Isolation and Determination of Tanshinone I, Cryptotanshinone, Tanshinone IIA in Danshen (Salvia miltiorrhiza B.) by Ultra Performance Liquid Chromatography (UPLC-DAD) - Doan, Manh Dung; Dang, Thi Ngan; Nguyen, Thi Hue; Le, Quoc Hung; Nguyen, Huu Tung; Nguyen, Dinh Luyen; Tran, Dinh Thang (Old Journal, 2019)
By chromatography, we isolated three principal compounds, tanshinone I, cryptotanshinone, tanshinone IIA from Danshen (Salvia miltiorrhiza B.). Their structures were determined on the basis of physicochemical data (^1H-NMR, ^13C-NMR and ESI-MS mass spectra). These compounds are purified (purity > 99.8%) by Agilent 218 purification system, which were used as standards for analyzing respective tanshinone I, cryptotanshinone and tanshinone IIA in six samples by the Ultra performance liquid chromatography (UPLC-DAD). In this study, we determined the content of tanshinone I, cryptotanshinone, tanshinone IIA in samples collected in different parts of Vietnam. The diterpen tanshinon compounds are the main active ingredients and are considered to be characteristic of Danshen in particular and Salvia species in general.